2020
DOI: 10.15408/sjie.v9i2.13751
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic Determinants of Under-Five Mortality Rate in Nigeria

Abstract: This paper examined the macroeconomic determinants of under-five mortality rate in Nigeria between 1980 and 2017. The study was predicated on the Grossman analytical framework rooted in the human capital development theory. A macro-econometric model incorporating major macroeconomic variables in explaining under-five mortality health outcomes. ARDL bound test estimation technique that took into consideration error correction mechanism was used. Tests of the model’s reliability were carried out using unit root … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The GDP per-capita was found to be positively significant, which indicates that a 1% increase in GDP per-capita leads to about a 2.5% increase in the under-five mortality rate in Malaysia. Almost all the relevant literature reviewed in this study reported either a negative relationship [ 18 , 25 ] or no significance [ 8 , 9 , 11 , 13 ]. Except for Kulkarni [ 15 ], whereby a positive, significant relationship was revealed between GDP per-capita and infant mortality rate in an analysis among BRICS countries (Brazil, Russia, India, China, and South Africa).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The GDP per-capita was found to be positively significant, which indicates that a 1% increase in GDP per-capita leads to about a 2.5% increase in the under-five mortality rate in Malaysia. Almost all the relevant literature reviewed in this study reported either a negative relationship [ 18 , 25 ] or no significance [ 8 , 9 , 11 , 13 ]. Except for Kulkarni [ 15 ], whereby a positive, significant relationship was revealed between GDP per-capita and infant mortality rate in an analysis among BRICS countries (Brazil, Russia, India, China, and South Africa).…”
Section: Resultsmentioning
confidence: 99%
“…Based on recent studies [ 8 , 9 , 11 , 12 , 25 ], the health capital model, as in Equation (1) is respecified by including the health expenditure ( and other control variables ( ), as follows: …”
Section: Methodology and Datamentioning
confidence: 99%
See 2 more Smart Citations
“…This increase has almost 1.89% increase on food sub-index which result by the rise in the prices of foods like cereals, bread, meats, rice, yam etc., this increment has Impact of critical macroeconomic drivers made almost everyone in the country to adjust or reduce the number of meals they take in a day and because of this, it is important at this point to determine the impact of this rise in inflation on the mortality rate of the country. Over the years, no significant progress has been made in Nigeria to reduce the increasing rate of mortality in the country, especially under-five mortality and maternal mortality (Agbatogun and Opeloyeru, 2020). The authors explored the macroeconomic variables that cause under-five mortality using secondary data from 1980 to 2017 in Nigeria, the autoregressive distributed lag model was used.…”
Section: Empirical Reviewmentioning
confidence: 99%